2020
DOI: 10.3389/fped.2020.00320
|View full text |Cite
|
Sign up to set email alerts
|

A Novel HNF4A Mutation Causing Three Phenotypic Forms of Glucose Dysregulation in a Family

Abstract: Maturity-onset diabetes of the young (MODY) classically describes dominantly inherited forms of monogenic diabetes diagnosed before 25 years of age due to pancreatic β-cell dysfunction. In contrast, mutations in certain MODY genes can also present with transient or persistent hyperinsulinemic hypoglycemia in newborn infants, reflecting instead β-cell dysregulation. Of the MODY genes described to date, only hepatocyte nuclear factor-4-alpha ( HNF4A ; MODY1) and hepatocyte nuclear factor-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Even though patients with MODY were found to differ from T1DM patients in several clinical predictors, such as C-peptide concentration [ 114 ], hsCRP [ 115 , 116 , 117 ], lipid levels, polyuria or age at diagnosis, still around 38% of the MODY patients are misdiagnosed with T1DM or T2DM [ 27 , 87 , 118 , 119 , 120 ]. In 2013 Steele et al reported that age-related glycated haemoglobin (HbA1c) reference ranges can be used as diagnostic criteria for GCK-MODY discriminator [ 121 ].…”
Section: Diagnosis and Current Treatment Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though patients with MODY were found to differ from T1DM patients in several clinical predictors, such as C-peptide concentration [ 114 ], hsCRP [ 115 , 116 , 117 ], lipid levels, polyuria or age at diagnosis, still around 38% of the MODY patients are misdiagnosed with T1DM or T2DM [ 27 , 87 , 118 , 119 , 120 ]. In 2013 Steele et al reported that age-related glycated haemoglobin (HbA1c) reference ranges can be used as diagnostic criteria for GCK-MODY discriminator [ 121 ].…”
Section: Diagnosis and Current Treatment Optionsmentioning
confidence: 99%
“…To complicate matters further, some MODY types have similar pathology, which can also lead to misdiagnosis. Some symptoms of HNF4A-MODY, such as transient neonatal hyperinsulinemic hypoglycaemia, progressive insulin secretory defect or microvascular complications, are very similar to symptoms observed in patients with HNF1A-MODY [ 119 , 125 , 126 ]. Due to these very similar phenotypes, and because HNF1A-MODY is more prevalent, some HNF4A-MODY cases may be incorrectly recognised as HNF1A-MODY.…”
Section: Diagnosis and Current Treatment Optionsmentioning
confidence: 99%
“…Alternatively, in addition to the paternally inherited HNF4A mutation, the T2DM susceptibility gene from the proband’s maternal grandfather may contribute to the severe clinical phenotype of this proband. In addition, the clinical phenotype of MODY1 varied in patients with different HNF4A mutations and even within the family members carrying the same mutation, and the younger generation in multigenerational families frequently exhibited an earlier age of onset and more severe phenotypes ( 5 , 11 , 12 ). Age-related penetrance of diabetes has been reported; for example, by the age of 40 years, 98% of probands and 76% of family members developed diabetes, and by the age of 50 years, 99% of probands and 90% of family members developed diabetes ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Roughly 50% of HNF4A -MODY patients have neonatal macrosomia, which paradoxically arises from transient hyperinsulinemic hypoglycemia (HH) during birth ( 10 ). Despite these distinguishing features, targeted sequencing of HNF4A based on clinical features may lead to misdiagnosis due to the absence of the classic presentation of HNF4A -MODY in some cases ( 11 , 12 ). Individuals with HNF4A -MODY have increased sensitivity to sulfonylureas, and low doses of sulfonylureas produced better glucose control than metformin in those patients ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Patients are born with hyperinsulinemia and increased body size, but it is not until they are older that their pancreas fails to secrete insulin in response to elevated blood glucose (7). These clinical findings highlighted the role of HNF4a in glucose metabolism (and insulin secretion) but many questions remain about the MODY1 mutations and the precise role of the different HNF4a isoforms in basic metabolism (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%